The unique consequences of feeling lucky: Implications for consumer behavior - Jiang, Yuwei; Cho, Angela; Adaval, Rashmi (Journal of Consumer Psychology, 2009)
AbstractCognitive priming procedures were used to identify the unique effects that luck‐related concepts have on consumer behavior. The effects of these concepts could theoretically influence behavior through the elicitation of positive affect or via temporary changes in participants' self representations of how lucky they feel. An initial experiment showed that priming Asian consumers with lucky numbers independently influenced both their perceptions of personal luck and the positive affect they reported experiencing. Subsequent experiments, however, showed that the effect of these primes on consumer behavior was mediated by momentary changes in how lucky people felt (i.e. changes in the self concept) rather than by the positive affect they were experiencing at the time. Exposing consumers to lucky numbers influenced their estimates of how likely they were to win a lottery (Experiment 2), their willingness to participate in such a lottery (Experiment 4), their evaluations of different promotional strategies (Experiment 3), and also the amount of money they were willing to invest in different financial options (Experiment 4). The effect of luck on behavior was also moderated by a person's regulatory focus.